Ofício do magistrado do distrito de Xiangshan, Yang, ao procurador de Macau, sobre o pagamento do foro do chão do território de Macau, no ano 41 do reinado de Qianlong (1776) (1776)
This abstract describes an imperial mandate issued on the 14th day of the 11th lunar month in Qianlong 41 (28 November 1776) by Yang, Magistrate of Xiangshan County, Guangzhou Prefecture, holding the rank of *Zhèng Bāpǐn* with five additional promotions and eight commendations, concerning the urgent collection of land rents and grain-tax silver from the Macau (*Háojìng Ào*) enclave. The document, bearing the official seal of the Magistrate’s Clerk (*Diǎnshǐ*) of Xiangshan County, addresses the Western (Portuguese) Community Magistrates—including *Duo Luo Gan*—as foreign headmen (*Yí Mù*), directing them to complete immediate and full collection of the outstanding Qianlong 41 tax revenues and remit the silver without delay to the Xiangshan County office. It specifies that these funds, traditionally recorded in the *Dīng-Dì* (‘Population-and-Land’) tax registers and forwarded to the provincial treasury, were required for disbursement as soldiers’ stipends via the provincial military paymaster. The mandate was received and registered in the Waiting Office (*Chéng Hòu Fáng*) and bears multiple official endorsements, including ‘Approved’ (*Pī*) and marginalia indicating Xiangshan County and a submission deadline. Archival reference numbers ‘483 T59 1976’ appear repeatedly, with handwritten annotation ‘T59’ confirming its classification. This primary source provides direct evidence of Qing administrative oversight of Macau’s fiscal obligations during the late eighteenth century and reflects formal Sino-Portuguese administrative interaction under imperial jurisdiction.
Keywords: Diǎnshǐ seal; Grain-tax silver; Háojìng Ào enclave; Imperial Mandate; Macau land rent collection; Portuguese community magistrates; Qing Dynasty local administration; Transcription; Xiangshan County magistrate; Zhèng Bāpǐn rank